The critical success factors for information system (IS) risk management implementation in the Nigerian banking sector - Fasilat, Sanusi (2015)
Information system (IS) risk management is an important area of study in the banking sector. Banks are service-oriented businesses that deal with the multitudes of customers and other stakeholders’ information on a daily basis. This information is, however, subjected to a number of uncertainty, threat, and risk. Hence, IS risk management implementation becomes a necessity. The objectives of this study are to identify the critical success factors for IS risk management implementation and to examine the effect of IS risk management implementation on bank performance. The critical success factors for IS risk management implementation covers both internal (i.e., top management commitment and support, organization structure, organization culture, trust, strategy, and resources) and external (i.e., competitive pressure) factors. Survey questionnaire is employed for data collection. The respondents involve 30 senior managers of the Nigerian banks. SPSS is used for data analysis. The findings show that top management commitment and support, organization structure, and resources significantly influence IS risk management implementation. Organization culture, trust, strategy, and competitive pressure, however, do not influence the IS risk management implementation. In addition, IS risk management implementation influences bank performance. The study’s findings contribute to the body of literature on the critical success factors for IS risk management implementation in the banking sector